Chinese business landscapes and strategies - Liu, Hong (Routledge, 2009)
Providing students and businesspeople with information on business in China, this guide features a mix of theoretical, academic and practical perspectives. It offers a wide view of industry structures and the competitive landscape, and provides a framework for Western companies to develop business and marketing strategies.